Kreowanie wizerunku przedsiębiorstwa elementem zarządzania strategicznego - Jakubów, Leon (Creating business image as a strategic management component, 2006)
Negative results of development and civilisational threats generate criticism directed at businesses and decrease trust in them. As a result people demand higher corporate social responsibility. To meet these expectations businesses appoint public relations departments whose task is to create a positive business image. Concern about good reputation and credibility of the company should not rely on sponsoring, charity work and good press relations. The main tasks of such a department should be to analyze future social expectations and to include them in the strategic goals of the company.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1137, s. 57-62